Cellular defence and innate immunity in the larval ovarian disc and differentiated ovariole of the silkworm Bombyx mori induced by microsporidian infection. Issue 1 (2nd January 2020) - Hungund, Shambhavi Prabhuling; Pradeep, Appukuttan Nair R.; Makwana, Pooja; Sagar, Chandrashekhar; Mishra, Rakesh K.
ABSTRACT: Activation of cellular defence and immunity in the ovary is critical to protect it from pathogenic infection. In this study cellular and innate immunity in larval and pupal ovaries of Bombyx mori induced by the microsporidian Nosema bombycis is reported. Autophagic vacuoles enclosing spores in flat cells of the larval ovarian disc revealed cellular defence. In the follicular epithelium of differentiated previtellogenic ovarioles of infected pupae, a network of RER and phagosomes observed probably to maintain cellular homeostasis. In larval and pupal ovaries, paralytic peptide titre, tyrosine content and phenoloxidase activity were enhanced revealing greater melanisation, which was confirmed by activation of melanisation genes, DDC, prophenoloxidase activating enzyme, prophenoloxidase 1 ( PPO1 ) and PPO2 after infection. βGRP-2, βGRP-4, CTL-11, Humoral lectin, Toll-6, Spätzle, Cactus, Relish, Pelle, and Dorsal genes showed differential expression in infected larval and pupal ovaries. Pupal ovarioles showed decreased expression and lower Spätzle titre than the larval ovary revealing suppression of innate immunity in the pupal ovary. Dorsal showed decreased expression, however, Pelle enhanced expression to maintain immunity through alternate components in differentiated ovarioles. Our data showed that coupled with cellular defence reactions, innate immune reactions and melanisation are activated in the developing ovary to defend against N. bombycis infection.